Physicochemical Characterization of the Oral Biotherapeutic Drug IMUNOR® - Jitka Mucksová; Gabriela Borošová; Miloš Blazsek; Jiří Kalina; Lucie Minaříková; Zdeňka Svobodová (MDPI AG, 2024)
IMUNOR is an oral biotherapeutic drug that had been developed, registered, and approved in 1997 in the Czech Republic and Slovakia. IMUNOR is a dialyzable leukocyte extract (DLE) prepared from swine leukocytes. It is characterized as a mixture of small peptides with molecular weights smaller than 12 kDa and a specific portion of nucleotides. The medical uses of IMUNOR include therapeutic applications within its registered range of indications, primarily for the treatment of immunodeficiencies, allergies, and certain acute or relapsing bacterial infections in adults and children. Despite the long-term clinical application of DLE, with strong evidence of positive therapeutic effects and no serious side effects, a detailed physicochemical specification of this mixture was lacking. We developed several methods for more in-depth physicochemical characterization of IMUNOR, including a spectrophotometric method for quantification of the total protein concentration and total DNA concentration in a mixture, several chromatographic methods for identification of individual components present in significant concentrations in IMUNOR, such as HPLC methods and the Sodium Dodecyl Sulphate Polyacrylamide Gel Electrophoresis method, and characterization of amino acid composition of this mixture. For the investigation of the variability among different batches of IMUNOR, five to nine representative batches from a standard manufacturing process on an industrial scale were utilized. Using the analytical methods, we verified and confirmed the batch-to-batch reproducibility of the biological product IMUNOR.